ChemInform Abstract: The Importance of the Self‐Assembly Process to Control Mechanical Properties of Low Molecular Weight Hydrogels. Issue 36 (15th August 2013) - Raeburn, Jaclyn; Cardoso, Andre Zamith; Adams, Dave J.
Abstract Review: 57 refs.